ALGORITHM FOR SELECTING A TREATMENT METHOD FOR PROXIMAL HUMERUS FRACTURES (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
optimization of approaches to surgical treatment of proximal humerus fractures and tactics of implant selection for various types of proximal humerus fractures.